Análisis de las rutinas periodísticas durante la fase uno del covid-19 de los medios digitales aldia.com.ec y El Vocero - Vera Alcivar, Zoila Denisse (2020)
The Covid-19 pandemic has led several countries and regions to decree quarantines or curfews, but maintaining information constantly and remotely has been a challenge for communicators due to the tough transition of the world. The digital media equipped dynamics to work as a team and generate content. However, the present case study is intended to understand the professional journalistic practices and routines of the digital media Aldia.com and El Vocero, which were in the first line of information regarding the first phase of the coronavirus in the Babahoyo canton. In addition to knowing how these changes influenced his media agenda. For which qualitative research, observation and interview were used. The latter resulted in journalists' difficulties in adapting to the new situation the world is going through.